Identification of a novel variant in N-cadherin associated with dilated cardiomyopathy - Chen, Yuanying; Sun, Qiqing; Hao, Chanjuan; Guo, Ruolan; Wang, Chentong; Yang, Weili; Zhang, Yaodong; Wang, Fangjie; Li, Wei; Guo, Jun (Frontiers in Medicine, 2022)
Background Dilated cardiomyopathy (DCM), which is a major cause of heart failure, is a primary cardiac muscle disease with high morbidity and mortality rates. DCM is a genetically heritable disease and more than 10 gene ontologies have been implicated in DCM. CDH2 encodes N-cadherin and belongs to a superfamily of transmembrane proteins that mediate cell–cell adhesion in a calcium-dependent manner. Deficiency of CDH2 is associated with arrhythmogenic right ventricular cardiomyopathy (OMIM: 618920) and agenesis of the corpus callosum, cardiac, ocular, and genital syndrome (OMIM: 618929). However, there have been no reports of isolated DCM associated with CDH2 deficiency. Methods We performed whole exome sequencing in a 12-year-old girl with non-syndromic DCM and her unaffected parents. Variants in both known DCM-related genes and novel candidate genes were analyzed and pathogenicity confirmation experiments were performed. Results No pathogenic/likely pathogenic variant in known DCM-related genes was identified in the patient. We found a de novo variant in a candidate gene CDH2 in the patient, namely, c.474G>C/p.Lys158Asn (NM_001792.5). This variant has not been reported in the ClinVar or Human Gene Mutation Database (HGMD). CDH2 p.Lys158Asn was found in the conserved domain of N-cadherin, which is associated with the hydrolysis of the precursor segment and interference with adhesiveness. Furthermore, we tested the expression and efficiency of cell–cell adhesion while overexpressing the CDH2 Lys158Asn mutant and two previously reported variants in CDH2 as positive controls. The adhesion efficiency was considerably reduced in the presence of the mutated CDH2 protein compared with wild-type CDH2 protein, which suggested that the mutated CDH2 protein's adhesion capacity was impaired. The variant was probably pathogenic after integrating clinical manifestations, genetic analysis, and functional tests. Conclusion We identified a CDH2 variant in DCM. We observed a new clinical symptom associated with N-cadherin deficiency and broadened the genetic spectra of DCM.